Improved Method of Springback Compensation in Metal Forming Analysis - Balon, P; Świątoniowski, A.; Szostak, J. (Проблемы прочности, 2016)
This paper presents an innovative compensation method for both forming and trimming die for the construction of vehicle parts manufactured by a transfer press. This method allows one to optimize the accuracy of compensation, consequently reducing springback in a more exact way than currently used methods, which account only for the influence of trimming on springback without generating compensated surfaces for the trimming die and the next forming operation. Moreover, there is a possibility to include the positioning effect during multioperation forming because of the huge impact of results on separate operations. When the positioning is not considered between operations there are problems with a proper shape even if the final part has the correct geometry. These problems generate some additional costs during the die production, which can be avoided by using the multioperation compensation.